2000
DOI: 10.1046/j.1460-9592.2000.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent anaphylactic reaction after induction with thiopentone and cisatracurium

Abstract: A 6-year-old boy presented for surgery for phimosis. The anaesthetic technique included intravenous induction with thiopentone and neuromuscular blockade with cisatracurium. Severe persistent bronchospasm and central cyanosis followed the administration of these drugs. A continuous i.v. infusion of epinephrine at 0.2 microg. kg(-1) x min(-1) was necessary to break the severe refractory bronchial hyperresponsiveness. There was no previous exposure to anaesthetic drugs and no definite family history of allergy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In children, the most frequent symptoms were respiratory (coughing, wheezing, bronchospasms, respiratory insufficiency), contrary to the data reported in adults, where the frequency was equivalent to only 40% in perioperative anaphylactic reactions [48]. The observable difference in respiratory symptoms is due, to patient atopy (where coexistent allergic asthma could be associated), which was observable in some cases and could undervalue the risks of the patient [20,21]. Likewise, emphasizing latex as a volatile allergen could favor respiratory signs, such as bronchospasms.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…In children, the most frequent symptoms were respiratory (coughing, wheezing, bronchospasms, respiratory insufficiency), contrary to the data reported in adults, where the frequency was equivalent to only 40% in perioperative anaphylactic reactions [48]. The observable difference in respiratory symptoms is due, to patient atopy (where coexistent allergic asthma could be associated), which was observable in some cases and could undervalue the risks of the patient [20,21]. Likewise, emphasizing latex as a volatile allergen could favor respiratory signs, such as bronchospasms.…”
mentioning
confidence: 79%
“…(Table 2) [17,18,20,23,24]. Also, when the reactions were related to latex, most reports were carried out using an adequate allergological evaluation [12,28,29,[32][33][34]36,37,[39][40][41]74].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Early clinical reports suggested that cisatracurium has negligible histamine-releasing potential and is a less potent trigger of allergic reactions than other NMBAs [3]. However, since 1995, several cases of cisatracurium-induced anaphylactic reactions with severe symptoms of cardiovascular collapse and bronchospasm have been reported [4-7]. …”
Section: Discussionmentioning
confidence: 99%
“…Cisatracurium, a relatively new NMBA, is a stereoisomer of atracurium, which does not induce apparent histamine release upon a bolus administration and causes fewer allergic reactions than other NMBAs [3]. However, several cases of anaphylactic reactions of varying severity to cisatracurium have been reported [4-7]. Two cases of severe anaphylactic reactions after cisatracurium administration are reported here.…”
mentioning
confidence: 99%